Inverse Levels of Adiponectin in Type 1 and Type 2 Diabetes Are in Accordance with the State of Albuminuria - Spomenka Ljubic; Anamarija Jazbec; Martina Tomic; Ante Piljac; Dubravka Jurisic Erzen; Branko Novak; Snjezana Kastelan; Marijana Vucic Lovrencic; Neva Brkljacic (International Journal of Endocrinology)
Aims. To investigate the behaviour of adiponectin (ApN) in patients with type 1 and type 2 diabetic nephropathy. Methods. ApN and inflammatory and other markers of the metabolic syndrome were compared across diabetes types, albumin excretion rate (AER), and creatinine clearance (CrCl) categories in 219 type 1 and type 2 diabetic patients. Results. Significant differences among ApN levels according to AER were found in both types of diabetes (F=8.45, df=2, P<0.001). With the progression of albuminuria, ApN increased in type 1 and decreased in type 2 diabetes. Patients with decreased CrCl had higher ApN levels than those with normal CrCl in either type of diabetes (F=12.7, df=1, P<0.001). The best model for ApN (R2=0.9002) obtained from stepwise regression in type 1 diabetes included CrCl, BMI, WBC, CRP, and age, while in type 2 diabetes (R2=0.2882) it included ppPG, LDL, and UA. Conclusion. ApN behaved differently in relation to albuminuria, increasing with its progression in type 1 diabetes and decreasing in type 2 diabetes. It was however increased in the subgroups with decreased CrCl in both types of diabetes. Albuminuria seems to be more important than renal insufficiency in the definition of ApN levels in type 1 and type 2 diabetes.